Relationship between Anti-Müllerian hormone, antral follicular population and resumption of cyclicity in postpartum buffaloes - M, KAVYA K; K, SHARMA R; A, JEROME; K, PHULIA S; I, SINGH (The Indian Journal of Animal Sciences, 2020)
The present study was designed to determine the relationship between Anti-Müllerian hormone (AMH) and antral follicular population (AFP), milk yield (MY), body weight (BW), body condition score (BCS) and resumption of cyclicity (RC) in postpartum buffaloes. For the present study, 20 buffaloes divided into 2 groups: Group I (n=10): buffaloes resuming cyclicity <30 days of calving; Group II (n=10): anestrous buffaloes >90 days postpartum. Blood sampling was carried out in all buffaloes in both groups at day 30 postpartum (day 0 considered as calving day). BW and BCS were monitored fortnightly and MY was recorded every week during first month of lactation. In this study, we found that none of the parameters (AMH, MY, BW and BCS) differed significantly, though RC differed between the two groups based on cyclicity, monitored using transrectal ultrasonography. In addition, AFP between the two groups (A: 19.7±4.95 vs 15.7±5.08) showed a trend in difference, though non-significant. Correlation study between the parameters, i.e. AMH, AFP, MY, BW, BCS and RC in postpartum buffaloes revealed nonsignificant correlation between AMH with AFP, MY, BW, BCS and RC in postpartum buffaloes. In summary, this study failed to deduce any relationship between AMH with AFP, MY, BW, BCS and RC in postpartum buffaloes.